PENINGKATAN KEMAMPUAN MENGENAL ANGKA MELALUI PERMAINAN MENJEPIT DI RA TUNAS BANGSA SIDOGEMAH SAYUNG DEMAK - Mualifah; Fu’ad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2025)
The background of this research problem is that the learning process that has been carried out so far does not make children more comfortable in learning, which should implement learning activities while playing. Therefore, researchers apply learning activities to recognize numbers through pinching games, aiming that children can receive learning without feeling pressured and are able to improve children's arithmetic skills well. The research method used is Classroom Action Research (CAR) with data collection techniques through observation, interviews and documentation techniques, as research subjects are group B students aged 5 to 6 years at RA Tunas Bangsa Sidogemah Sayung Demak with a total of 41 children, namely 14 boys and 27 girls. The results of the study revealed that: the implementation of research in children's arithmetic skills was carried out by repeating four times and carried out through four stages each meeting. The four stages are: planning, implementing actions (acting), observation and reflection. The improvement of numeracy skills through the number drying game for children of RA Tunas Bangsa Sidogemah Sayung Demak in the pre-cycle reached 46.6% in the category of starting to develop, Cycle I reached 61.2% in the category of Developing According to Expectations. While in Cycle II it reached 76% in the category of Developing Very Well (BSB), so this number drying game is very suitable to be applied to children.